2021
DOI: 10.1021/acsaelm.1c00802
|View full text |Cite
|
Sign up to set email alerts
|

Airbrushed PVDF–TrFE Fibrous Sensors for E-Textiles

Abstract: The low-temperature processing, inherent flexibility, and biocompatibility of piezoelectric polymers such as poly(vinylidene fluoride) (PVDF)-based materials enable the creation of soft wearable sensors, energy harvesters, and actuators. Of the various processing techniques, electrospinning is the most widely adopted process to form PVDF nanofiber scaffolds with enhanced piezoelectric properties such that they do not require further post-processing such as mechanical drawing, electrical poling, or thermal anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…It finally forms self-poled nanofibers under the electric field between the tip and the collector. [85][86][87] Li et al 88 found that the polymer solution is stretched by electrostatic force, which leads to the high orientation of the molecular chain in axial direction of the fiber and significantly enhances the crystallinity of the electrospun P(VDF-TrFE) fibers.…”
Section: Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It finally forms self-poled nanofibers under the electric field between the tip and the collector. [85][86][87] Li et al 88 found that the polymer solution is stretched by electrostatic force, which leads to the high orientation of the molecular chain in axial direction of the fiber and significantly enhances the crystallinity of the electrospun P(VDF-TrFE) fibers.…”
Section: Electric Fieldmentioning
confidence: 99%
“…The crystallinity can also be significantly tuned by electrical poling. After poling treatment (Figure 4A), the electric dipoles adopt the same alignment along a specific direction (such as the direction of the electric field) and thereby the molecular chains are arranged in order, which are in favor of the improvement of crystallinity 62,77–100 . Various approaches have been proposed to apply the electric field on P(VDF‐TrFE) films.…”
Section: Influencing Factors On the Crystallinitymentioning
confidence: 99%
“…Thus, if there are high requirements for flexibility, breathability, or even elasticity, it is better to define the form of the fibers. In this case, such a nanogenerator finds perfect use in the field of tissue engineering [45], smart textiles [46], or as an active filter [47]. Otherwise, layers or rather thinner films can be used, for example, as a pressure sensor [48,49].…”
Section: Materials Fabricationmentioning
confidence: 99%
“…However, low Curie transition temperatures ( T c ) (ranging from 80 to 140 °C, depending on the molar ratio of VDF and TrFE units), poor thermal stability, and high cost (almost 10 times higher than that of PVDF) of P­(VDF-TrFE) hinder its industrial bath production for commercial applications . On the contrary, PVDF exhibits good thermal stability due to the physical absence of T c , which suggests considerable potential for memory device applications . Therefore, special consideration has been given to the fabrication of nanoscale β-PVDF thin films.…”
Section: Introductionmentioning
confidence: 99%
“…22 On the contrary, PVDF exhibits good thermal stability due to the physical absence of T c , which suggests considerable potential for memory device applications. 23 Therefore, special consideration has been given to the fabrication of nanoscale β-PVDF thin films. The approaches based on the electrospray technique, low-pressure chemical vapor polymerization, ultrasonic atomization, high-pressure application, solution growth, nanocomposite formation, melt quenching, and high-pressure application have all been researched.…”
Section: ■ Introductionmentioning
confidence: 99%